Placenta praevia: percreta and accreta, our experience - Lewis, Preeti F.; Chinchoriya, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: morbidly adherent placenta has an increasing incidence over decades. The purpose of this study is to identify risk factors and etiology of placenta previa- accreta and percreta. Methods: A cross sectional observational study of patients with morbidly adherent placenta previa including placenta accreta and placenta percreta were studied over a period of three years from June 2017 to June 2019 in a tertiary care centre, Mumbai. Results: Cases showed a higher incidence in patients with previous cesarean delivery (CS), grandmultiparity, abortions without the history of check curettage and anterior/central placentae. Conclusions: History of uterine surgeries and previous cesarean are some important risk factors for accreta in placenta previa patients.